Preživetje bolnic z rakom jajčnikov - Zadnik, Vesna (Medicinski razgledi, 1999)
Data from 282 patients who were first treated tor epithelial ovarian malignomaat the Institute of Oncology and Gynecological clinic in Ljubljana between 1990 and 1992 were analysed retrospectively. The patients were followed through 1997. The survival rates were determined by Kaplan-Meier method. For establishment of hazard ratios Cox analysis used. The five-year survival rates for diferent factors are as follows: 74% for borderline and 38 for patierns with carcinoma; by stage (I-IV) 88, 48, 26 and 12 %; by cancer grades (1-3) 69, 49, 26% respectively. Concerning age 50 older patients survive five years in 31%, but younger in 61 %. The group with the diameter ofresidual implants after surgery smaller then 1 cm has 73% five- year survival, but the other group 18%. After multivariate analysis the prognostic factors which were still significant are: stage, age higher then 50, the diameter of residual implants after first surgery greater than 1 cm, and type of primary treatment for the whole cohort and the one of higher stages (III and IV). The type of primary treatment was not significant for the group with the lower stages (I and II) of cancer. An understanding of the influence of these prognostic factors on the survival rate in epithelial ovarian malignoma offers the opportunity to survey the situation in Slovenia and to compare our cohort with those in cancer centres throughout the world.
Keywords: ginekologija; Ovarian neoplasms; Pathology; rak (medicina); Therapy; jajčniki; Mortality; preživetje; Prognosis; Survival rate; Neoplasm staging; Age factors; Multivariate analysis